THE ROLE OF THE COMPETENCY-BASED APPROACH IN THE DEVELOPMENT OF THE PROFESSIONAL-ETHICAL CULTURE OF FUTURE TEACHERS (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the importance of the competency-based approach in developing the professional and ethical culture of future teachers. In the process of forming professional competencies, the issues of developing the ethical and normative foundations of pedagogical activity, professional values, responsibility, pedagogical ethics and communication culture are covered. Also, the theoretical and practical aspects of forming the skills of effective organization of professional activity, independent decision-making and adherence to ethical principles in the educational process in future teachers through the competency-based approach are revealed. The results of the study show that the competency-based approach is an important methodological basis in developing the professional and ethical culture of future teachers.
Keywords: Future teacher, professional and ethical culture, competency-based approach, pedagogical competence, pedagogical ethics, professional values, pedagogical skills, communicative competence, moral education, quality of education, professional development, pedagogical activity.